Tuning of conductive type and magnetic properties of Ca3Co2O6 ceramics through Pb‐doping. Issue 8 (21st April 2017) - Song, Jiyue; Zhao, Bangchuan; Huang, Yanan; Qin, Yanfeng; Song, Wenhai; Sun, Yuping
Abstract: The effect of Pb doping on structural, electrical, magnetic, and thermal transport properties of Ca3− x Pb x Co2 O6 ( x =0‐0.3) ceramics has been investigated systemically. It is found that the substituted Pb‐ions have a mixed valence state of +2 and +4, and a small amount of Co 3+ ions will transfer into Co 2+ due to the substitution of Pb 4+ for Ca 2+ . The resistivity decreases monotonically with increasing Pb content, which is related to the variation in carrier concentration and the enhanced grain connectivity. The signs of both Hall coefficient and thermopower changed from positive to negative by a proper Pb doping, indicating the conductive type of Ca3 Co2 O6 can be effectively tuned from p to n through the doping. The low‐temperature magnetization, the magnetic exchange coupling constant J and Weiss temperature θ decrease monotonically with the increase in Pb‐doping content, indicating the strength of the ferromagnetic interaction between adjacent high spin Co 3+ ions has been weakened due to the reduced magnetic correlation length in these Pb‐doped samples.